Aplicación de diseño de experimentos para el análisis de secado de un producto (Experiment design application for analysis of the drying a product) - Garza Villegas, Juan Baldemar (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract. The article presents a study of the painting of a product, to determine which factor levels minimizing waiting time for complete drying. An experiment was performed on 3 factors factorial with 2 levels each, the factors used were glaze type used (standard or quick-drying), drying method (with or without cold water) and the number of layers that apply (1 or 2 layers). 3 replicates were performed to remove ambiguities in the responses. In short, the paper presents the best combination of factor levels for painting product, that combination is malleable as to whether there is some level unchangeable in the process of painting.